Morphometrics of the Spinal Cord and Surrounding Structures in Alligator mississippiensis - Skye Greer; Michael J. Cramberg; Bruce A. Young (Biology, 2022)
Understanding the fluid dynamics of the cerebrospinal fluid requires a quantitative description of the spaces in which it flows, including the spinal cord and surrounding meninges. The morphometrics of the spinal cord and surrounding tissues were studied in specimens of the American alligator (Alligator mississippiensis) ranging from hatchlings through adults. Within any size class of alligators (i.e., hatchlings), along the axial length there are significant differences in the size of the spinal cord, meninges, and vertebral canal; these differences can be used to define discrete cervical, thoracic, lumbar and caudal regions. When compared across the range of body sizes in Alligator, every structure in each spinal region had a distinctive growth rate; thus, the physical arrangements between the structures changed as the alligator grew. The combination of regional differentiation and differential growth rates was particularly apparent in the lumbar meninges where a unique form of lumbar cistern could be identified and shown to decrease in relative size as the alligator ages. This analysis of the spinal cord and surrounding tissues was undertaken to develop a data set that could be used for computational flow dynamics of the crocodilian cerebrospinal fluid, and also to assist in the analysis of fossil archosaurs.